Direct Power Control Strategy of PWM Rectifier Based on Improved Virtual Flux-Linkage Observer - Wenshao BU; Leilei Xu (Journal of Control Science and Engineering)
In order to achieve the low cost and high performance control of three-phase PWM rectifier, a direct power control (DPC) strategy based on a new-style virtual flux-linkage observer is proposed. The model of three-phase PWM rectifier and the principle of virtual flux-linkage vector control are introduced firstly. Then, in order to avoid the effect of integral initial value and cumulative deviation, three first-order low-pass filters are cascaded to replace the pure integral link; an improved virtual flux-linkage observer of three-phase power grid is presented. From the observed virtual flux-linkage, the voltage and instantaneous power of three-phase power grid are online estimated. On this basis, the power grid voltage sensorless direct power control system of three-phase PWM rectifier is designed. Simulation results have shown that, both in the rectifying state and in the inverting state, the power grid side current and the DC side voltage of three-phase PWM rectifier all can be effectively controlled; the high power factor operation of three-phase PWM rectifier is realized.